Pemanfaatan Teknologi Informasi dalam Manajemen Persuratan di UPT Sekolah Dasar Negeri 064037 - Okta Elviana Manurung; Dina Oktapia; T. Darmansah; Lola Amalia Sibarani; Aji Pramudya (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2024)
This research aims to find out how effective and efficient correspondence management is after the use of online-based electronic information and communication technology (paperless office system) in processing incoming letters. Utilization of information technology in correspondence management is management of an agency's correspondence system by utilizing information technology in the form of computer media, the internet or other media using either manual or electronic systems. The main discussion in this research is how effective the delivery of incoming mail services is with an electronic system and the obstacles faced in implementing these two systems in mail management. The research results show that the application of information technology in correspondence management is able to speed up the administration process, reduce human error, and increase data accessibility and security. However, several obstacles such as limited skilled human resources and inadequate technological infrastructure are still challenges. Recommendations are provided to overcome these obstacles, including training for staff and improving technological infrastructure. Thus, it is hoped that the use of information technology in correspondence management can continue to be improved to support a more modern school administration and efficient.